Komunikasi Dakwah Habib Husein Ja'far dan Habib Bahar bin Smith Melalui Youtube - Pribadi, Anggun; Dwijayanto, Arik; Ansori, Teguh (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2023)
The existence of two well-known preachers Habib Bahar Bin Smith and Habib Husein Ja'far who have characteristics and methods of conveying their da'wah messages through YouTube Media is the background to the conduct of this research in which the two preachers have ways/methods of da'wah that are quite interesting to Habib Husein Ja's attention 'far with his preaching style according to millennials while Habib Bahar Bin Smit with his firm preaching style. This is of course a topic of conversation among the people besides that the style or narrative of da'wah becomes a competitive or competitive arena that has great capacity to be built by a preacher to spread ideas, ideas and interests, therefore a preacher has ways/methods of conveying Islamic teachings. The purpose of this research is to analyze how the da'wah communication between Habib Husein Ja'far and Habib Bahar Bin Smith is on YouTube social media. This study uses qualitative methods, in which data is collected from various reliable sources, such as articles, journals, and the internet. The results of this study indicate that humans find new ways or methods in finding sources of information and da'wah content that is shared through the YouTube social media owned by habib husein ja'far and habib bahar bin smith can fulfill the curiosity of the public. In this case the method / way of preaching is very important because it will determine the results you want to achieve.